Switching and mixing codes - Kun Mustain (UPT P2M Politeknik Negeri Malang, 2011)
The aim of this article is to provide an overview over the phenomenon of code‐switching and code‐mixing. The history of code change has undergone various periods that have shown the phenomenon of code switching and code‐mixing. In the research of code change it is clear that code‐switching and code‐mixing can be investigated from different perspectives. One can see that there is a unique phenomenon of how language is used. The Code‐mixing and codeswitching can deliberately occur both in informal and formal situation. These phenomena are connected to the varying motivations and purposes of code‐mixing and switching. The codes to be mixed and switched may be not only languages but also styles, or even dialects. The most important thing, in conducting code‐mixing and switching, speakers must select the code related to the social contexts and social dimensions.